2021
DOI: 10.3389/fpsyg.2021.683987
|View full text |Cite
|
Sign up to set email alerts
|

Protect ya Grandma! The Effects of Students' Epistemic Beliefs and Prosocial Values on COVID-19 Vaccination Intentions

Abstract: The present study investigates epistemic beliefs (beliefs about the nature of knowledge and knowing) and prosocial values as predictors of COVID-19 vaccination intentions. As a first hypothesis, we posit that beliefs in justification by authority will positively relate to vaccination intentions. Second, we expect a positive relationship between prosocial values and vaccination intentions. Third, we hypothesize that beliefs in justification by authority moderate the relationship between prosocial values and vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The results of this study are consistent with the findings of the study by Rosman et al (2021) that the credibility of public health experts, scientists, and doctors who confirm the safety and efficacy of vaccines greatly contribute to the success of vaccination.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of this study are consistent with the findings of the study by Rosman et al (2021) that the credibility of public health experts, scientists, and doctors who confirm the safety and efficacy of vaccines greatly contribute to the success of vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study also confirmed the conclusions by Rosman et al (2021) that, for European countries, doubts about the safety of a vaccine expressed by official authorities significantly reduce the willingness of the population to get vaccinated. Thus, in March 2021, the safety of the AstraZeneca vaccine was questioned; several countries suspended its use.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations